Internal Mammary Lymph Node Visualization as a Sentinel Sonographic Sign of Tuberculous Pleurisy - Messineo, Ludovico; Quadri, Federico; Valsecchi, Alberto; Lonni, Sara; Palmiotti, Antonio; Giampietro, Marchetti (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Background Tuberculous pleurisy is one of the primary sites of extrapulmonary tuberculosis, but clinicians currently lack the diagnostic tools necessary for early recognition in the absence of typical signs and symptoms. With this study, we aimed to test the association between internal mammary adenopathies and tuberculous pleurisy (TP).Methods 60 patients with a post-thoracoscopic histological diagnosis of granulomatosis or acute infective pleurisy were retrospectively enrolled. All of them had chest sonography and/or CT scan data available. At least two expert chest sonography physicians re-analyzed the sonography images to look for any internal mammary adenopathy. Such findings were compared to the CT data.Results Chest sonography showed internal mammary adenopathy ipsilateral to the pleural effusion in 97 % of 29 patients who had a diagnosis of TP, and in 13 % of those with an acute infective pleurisy (p < 0.001). Receiver operator characteristic analysis revealed 97 % sensitivity and 87 % specificity for this technique in predicting TP (area under curve 0.92 ± 0.04, p < 0.001). CT detection power and node measures were significantly similar (p < 0.001).Conclusion Sonographic internal mammary node visualization ipsilateral to the pleural effusion may become a sentinel sign for TP, contributing to early diagnosis or orienting the diagnostic management towards invasive procedures in uncertain cases.
Keywords: sentinel lymph node; granulomatous pleural diseases; pleural drainage